The Gambia : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for a Waiver of Nonobservance of Performance Criterion; Staff Report; and Press Release. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Fifth Review under the Poverty Reduction and Growth Facility (PRGF) for The Gambia. The Gambia's external debt position has worsened recently. The global economic crisis is undermining growth and the external balance. Performance on the PRGF-supported program has been generally satisfactory. All quantitative performance criteria for end-March 2009 were met, and the structural measures scheduled through March were implemented. IMF staff supports the authorities' request for a waiver for the nonobservance of the performance criterion for making the credit reference bureau operational.